TINJAUAN TENTANG PELAKSANAAN LAPORAN SENSUS HARIAN RAWAT INAP DI RS BHINEKA BAKTI HUSADA TANGERANG SELATAN - Ita Latho; Noviyanti Wahyu Lestari (Journal Of Applied Health Research And Development, 2020)
Background: one of the supporting factors of medical record is the making of long-stay daily census report long-stay that is aimed at obtaining information about the admission patient and discharged patient for 24 hours.The objective of research: is to find out about the implementation of long-stay daily census report at Bhineka Bhakti Husada hospital. The methodology of Research : this research used descriptive research. Data collecting used observation sheet and interview. Population in this research were 6 head of nursing room and 2 medical record staff who are in charge of the implementation of long-stay daily census report. Sampling technique in this research used purposive sampling. The result of Research: shows that the result from data sources are not compatible with (1) where the making of daily census in medical record obtaining data from daily census form, while in the nursing ward, obtained from medical record. Operational procedure standard in implementation of long-stay daily census report, there are three points that are compatible with the filling of the number of yesterday patients, the filling of data of patient admitted and discharged and the implementation of delivery of long-stay daily census. The delay factors in the implementation of long-stay daily census report are due to that nurses feel the delivery of long-stay daily census is not priority that must be carried out timely. Conclusions: Data sources used by nurses are not yet appropriate, Standard Operating Procedures on Implementation of Inpatient Daily Census Reports are in accordance with 40% and which are not yet 60%, Delay Factors in Implementing Inpatient Daily Census Reports from the treatment room to the medical record section are lack of discipline of nurses in hospitalized daily census deliveries.